Combined model of the EBMT score modified model and the HCT-CI improves the stratification of high-risk patients undergoing unmanipulated haploidentical blood and marrow transplantation. Issue 9 (1st September 2016) - Chang, Ying-Jun; Wang, Hong-Tao; Xu, Lan-Ping; Wang, Yu; Liu, Kai-Yan; Zhang, Xiao-Hui; Liu, Dai-Hong; Chen, Huan; Chen, Yu-Hong; Wang, Feng-Rong; Han, Wei-; Sun, Yu-Qian; et al.
Abstract: Both European Group for blood and marrow transplantation risk score (EBMT score modified model) and hematopoietic cell transplantation comorbidity index (HCT-CI) are suitable for evaluating patients undergoing unmanipulated haploidentical blood and marrow transplantation (HBMT), while the predictive capacity of the combined model following haploidentical transplantation is still unknown. In this study, we calculated and validated 322 consecutive unmanipulated HBMT patients. Patients in groups with HCT-CI scores of 0 or 1–2 exhibited similar overall survival (OS), non-relapse mortality (NRM), and relapse rates, independent of their EBMT score modified model. In the group in which patients' HCT-CI scores were ≥3, patients with high EBMT score modified model showed lower OS ( p = 0.003) and higher NRM ( p = 0.001) than did patients with low EBMT score. In conclusion, this combined model can be used to predict outcomes and may improve the stratification of high-risk patients following unmanipulated HBMT.